2004
DOI: 10.1103/physrevlett.92.197005
|View full text |Cite
|
Sign up to set email alerts
|

Softening of Cu-O Bond Stretching Phonons in TetragonalHgBa2CuO4+δ

Abstract: Phonons in nearly optimally doped HgBa(2)CuO(4+delta) were studied by inelastic x-ray scattering. The dispersion of the low-energy modes is well described by a shell model, while the Cu-O bond stretching mode at high energy shows strong softening towards the zone boundary, which deviates strongly from the model. This seems to be common in the hole-doped high-T(c) superconducting cuprates, and, based on this work, not related to a lattice distortion specific to each material.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 38 publications
9
81
0
Order By: Relevance
“…Again decades of research on network glasses have shown that the best weighting is the simplest, that is, equal weighting ( R ) for all atoms Advances in Condensed Matter Physics 5 provides the best description of glass-forming ability and the glass transition, because the overall network is mechanically marginally stable (MMS). As discussed earlier, shell-model calculations [31] of phonon spectra in HTSC are generally unable to predict very soft modes, especially those associated with dopants. Quite revealing is the fact that the fitted effective charges for "soft layer" rare earth cations in shell models of LSCO and YBCO phonon spectra derived from neutron scattering were inexplicably negative [32].…”
Section: Mms and Coarse Grainingmentioning
confidence: 99%
“…Again decades of research on network glasses have shown that the best weighting is the simplest, that is, equal weighting ( R ) for all atoms Advances in Condensed Matter Physics 5 provides the best description of glass-forming ability and the glass transition, because the overall network is mechanically marginally stable (MMS). As discussed earlier, shell-model calculations [31] of phonon spectra in HTSC are generally unable to predict very soft modes, especially those associated with dopants. Quite revealing is the fact that the fitted effective charges for "soft layer" rare earth cations in shell models of LSCO and YBCO phonon spectra derived from neutron scattering were inexplicably negative [32].…”
Section: Mms and Coarse Grainingmentioning
confidence: 99%
“…By contrast, in the high-T c superconducting cuprates (HTSCs), the phonon contribution to superconductivity remains unclear, although the high-frequency oxygen mode (Cu-O bond stretching mode) shows strong softening as the momentum transfer is changed [10][11][12][13][14][15][16][17] . The main subject of discussion for the cuprates is the rapid drop of the bond stretching phonon frequency, and increased in linewidth, in the (q, 0, 0) direction at q > 0.25, which is not reproduced by the LDA calculations 14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The lattice dynamics in Sr 2 RuO 4 merits further interest as a reference material for the large class of transition metal-oxides with a perovskite related structure where an anomalous phonon dispersion has been observed [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Stimulated by the phenomenon of high-temperature superconductivity the phonon dispersion of many oxide perovskites has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In particular in the insulating parent compounds, like La 2 CuO 4 , all features in the phonon dispersion are at least qualitatively described by simple ionic models. In electronically doped materials, like (La, Sr) 2 CuO 4 , however, significant discrepancies in the dispersion of the longitudinal bond-stretching branches were discovered [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. A typical lattice dynamical model including an isotropic screening function will always predict an increasing bondstretching dispersion when passing from the Brillouinzone center into the zone due to the imperfect screening of the Coulomb-potentials at short distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation